The impact of inadequate provision of mobility devices on the lives of physically disabled children in Tembalethu special school in the township of Gugulethu, Cape Town - Gcaza, Siphokazi (Division of Occupational Therapy, 2014)
In this qualitative study a case study approach was used out to explore and describe the perceptions of children with mobility impairments in Tembalethu Special School related to the effects of inadequate provision of assistive devices on their lives.